Factors Affecting the Performance of Hybrid Nanoﬂuids: A Comprehensive Review - Muhammad Haﬁz, Hamzah; Nor Azwadi, Che Sidik; Tan, Lit Ken; R., Mamat; Najafi, G. (Elsevier Ltd., 2017)
Hybrid nanoﬂuids have proven its favorable impact in terms of thermophysical properties, heat transfer rate and stability. Many distinctive features of hybrid nanoﬂuids offer an astonishing potential for many heat transfer applications. In this paper,we summarized the factors affecting the performance of hybrid nanoﬂuid in enhancing the thermal performance of heat transfer systems. The conclusions and important summaries were also presented according to the data collected.